Different paths towards autonomy: A comparison of the political status of the Faroe Islands and Iceland in the first half of the 19th century - Regin Winther Poulsen 1994- (2018)
This dissertation is a comparison of the political status of Iceland and the Faroe Islands within the Danish kingdom during the first half of the 19th century. Though they share a common history, the two dependencies took a radically different path towards autonomy during this period. Today Iceland is a republic while the Faroes still are a part of the Danish kingdom. This study examines the difference between the agendas of the two Danish dependencies in the Rigsdagen, the first Danish legislature, when it met for the first time in 1848 to discuss the first Danish constitution, the so-called Junigrundloven. In order to explain why the political agendas of the dependencies were so different, it is necessary to study in detail the years before 1848. The administration, trade and culture of the two dependencies are examined in order to provide the background for the discussion of the quite different political status Iceland and the Faroes had within the Danish kingdom. Furthermore, the debates in the Danish state assemblies regarding the re-establishment of the Alþingi in 1843 are discussed in comparison to the debates in the same assemblies regarding the re-establishment of the Løgting in 1844 and 1846. Even though the state assemblies received similar petitions from both dependencies, Alþingi was re-established in 1843, while the same did not happen with the Løgting in the Faroes. Finally, the debates in Rigsdagen are examined. The main goal is to establish, why the two North Atlantic dependencies of the Danish kingdom took such different paths towards autonomy, the result being that Iceland is now a sovereign republic while the Faroe Islands are still a part of Denmark, albeit with Home Rule.